The Presidents and the Constitution : a living history - Gormley, Ken (New York : New York University Press, 2016)
"In this sweepingly ambitious volume, the nation's foremost experts on the American presidency and the U.S. Constitution join together to tell the intertwined stories of how each American president has confronted and shaped the Constitution. Each occupant of the office--the first president to the forty-fourth--has contributed to the story of the Constitution through the decisions he made and the actions he took as the nation's chief executive. By examining presidential history through the lens of constitutional conflicts and challenges, The Presidents and the Constitution offers a fresh perspective on how the Constitution has evolved in the hands of individual presidents. It delves into key moments in American history, from Washington's early battles with Congress to the advent of the national security presidency under George W. Bush and Barack Obama, to reveal the dramatic historical forces that drove these presidents to action. Historians and legal experts, including Richard Ellis, Gary Hart, Stanley Kutler and Kenneth Starr, bring the Constitution to life, and show how the awesome powers of the American presidency have been shaped by the men who were granted them. The book brings to the fore the overarching constitutional themes that span this country's history and ties together presidencies in a way never before accomplished."--Book jacket.
Introduction: An unfinished presidency / Ken Gormley -- Pt. I. The founding era : George Washington / Richard J. Ellis ; John Adams / Louis Fisher ; Thomas Jefferson / Cliff Sloan, Louis Fisher, and Moshe Spinowitz ; James Madison / Ralph Ketcham ; James Monroe / Gary Hart ; John Quincy Adams / Jonathan L. Entin -- Pt. II. The Age of Jackson : Andrew Jackson / Mark A. Graber ; Martin Van Buren / Michael J. Gerhardt ; William Henry Harrison / David Marks Shribman ; John Tyler / Robert J. Spitzer ; James K. Polk / Frank J. Williams -- Pt. III. The pre-Civil War era : Zachary Taylor / Paul Finkelman ; Millard Fillmore / Joseph F. Rishel ; Franklin Pierce / Paul Finkelman ; James Buchanan / Thomas A. Horrocks -- Pt. IV. Civil War and Reconstruction : Abraham Lincoln / William D. Pederson ; Andrew Johnson / Michael Les Benedict ; Ulysses S. Grant / John F. Marszalek -- Pt. V. The Gilded Age : Rutherford B. Hayes / Michael A. Ross ; James A. Garfield / Thomas C. Sutton ; Chester A. Arthur / Thomas C. Sutton ; Grover Cleveland, first term: 1884-1888 / Donald Grier Stephenson Jr. ; Benjamin Harrison / Allan B. Spetter ; Grover Cleveland, second term / Donald Grier Stephenson Jr. ; William McKinley / Thomas C. Sutton -- Pt. VI. The Progressive Era : Theodore Roosevelt / William D. Bader ; William Howard Taft / Francine Sanders Romero -- Pt. VII. World War I and the Great Depression : Woodrow Wilson / Saladin M. Ambar : Warren G. Harding / James D. Robenalt ; Calvin Coolidge / John W. Johnson and Dale E. P. Yurs ; Herbert Hoover / John Q. Barrett -- Pt. VIII. The New Deal and World War II : Franklin Delano Roosevelt / William D. Pederson ; Harry S. Truman / James N. Giglio -- Pt. IX. The Civil Rights Era : Dwight D. Eisenhower / Richard V. Damms ; John F. Kennedy / Barbara A. Perry ; Lyndon B. Johnson / John L. Bullion -- Pt. X. The Watergate Era and reform : Richard M. Nixon / Stanley Kutler ; Gerald R. Ford / Jeffrey Crouch ; Jimmy Carter / Scott Kaufman -- Pt. XI. New conservatives, new Democrats, and polarization : Ronald Reagan / Kenneth W. Starr ; George H. W. Bush / Lori Cox Han ; William Jefferson Clinton / Ken Gormley -- Pt. XII. National security era: post-9/11 : George W. Bush / Benjamin A. Kleinerman : Barack Obama / Michael J. Gerhardt -- Conclusion: An evolving American presidency / Ken Gormley.
Includes bibliographical references and index.
Keywords: Executive power -- United States -- History; Presidents -- United States -- History; Constitutional history -- United States